Sistem Pengontrolan Temperatur ON-OFF Menggunakan Mikrokontroler AT89C51 dengan Pengindera Termokopel - Syufrawardi, Syufrawardi; Yohandri, Yohandri; Asrizal, Asrizal (Sainstek, 2008)
Temperature control system was an important instrument to control temperature of an object at setpoint temperature and many applications in human life. Investigation of control system was required to get high quality of system. Purposes of this research was: to investigate relation between output voltage of sensor and signal processing circuits with temperature, to determine number that presented at digital display as function of temperature, and to determine accuracy and precision of temperature control system. The research can be classified into laboratory experimental research. Data collecting technique that used in this research was direct measurement. Variables that measured temperature, output voltage of sensor, and output voltage of amplifier circuits, while gradient of straight line and static characteristics were measured indirectly. The data that  founded of measurement result was analyzed  by using graph and error analysis. Graph analysis was used to determine measurement error, accuracy, and precision of control system. There were four main results of this research as follow: 1). Output voltage of sensor  increase directly proportional with temperature and sensitivity of sensor was 0,042 Volt/oC, 2). Output voltage of differential and non inverting amplifier  also directly proportional with temperature, each of  it’s gradient was 0,0091 Volt/oC and 0,0248 V/oC, 3). The number that displayed at seven segment before linearization process directly proportional with temperature and after processing the number at digital display was suitable with temperature that measured by standard digital thermometer, and 4). The average of accuracy and precision of temperature control system by using microcontroller with thermocouple  sensing was high, each of it was 0,9967 and 0,997 in order of least significant scale was 1 oC. Key words : Control system, thermocouple, microcontroller, sensitivity, accuracy, precision.